1995
DOI: 10.1111/j.1600-0560.1995.tb01412.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of p53 expression in dermatofibrosarcoma protuberans and dermatofibroma: Lack of correlation with proliferation rate

Abstract: p53 protein plays an important role in control of cell proliferation by suppressing proliferation of cells with DNA damage. Mutations of the p53 gene increase the stability of the encoded nonfunctional protein which accumulates in the nuclei, allowing it to be detectable by immunohistochemistry. Mutant p53 protein has been observed in preneoplastic and neoplastic conditions supporting its role in the development of some human cancers. In this immunohistochemical study, we examined p53 expression in 12 Dermatof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 23 publications
0
6
1
1
Order By: Relevance
“…6,7 Hisaoka et al 7 investigated p53 mutations in 18 cases of DFSP, including 5 cases with a fibrosarcomatous area, and observed missense mutations in 1 case with a fibrosarcomatous area. However, to determine whether p53 mutation is actually associated with tumor progression, it is necessary to dissect ordinary DFSP and fibrosarcomatous areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Hisaoka et al 7 investigated p53 mutations in 18 cases of DFSP, including 5 cases with a fibrosarcomatous area, and observed missense mutations in 1 case with a fibrosarcomatous area. However, to determine whether p53 mutation is actually associated with tumor progression, it is necessary to dissect ordinary DFSP and fibrosarcomatous areas.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors with fibrosarcoma or MFH areas are thought to behave more aggressively than ordinary DFSP. [1][2][3][4][5] Some studies have suggested that alteration in the p53 pathway is involved in a fibrosarcomatous transformation, 6,7 but other molecular mechanisms have not been well studied.…”
mentioning
confidence: 99%
“…p53 Mutations and expression changes are common to many cancers and have long been suspected in DFSP pathogenesis because of the p53 gene's location on the frequently translocated 17th chromosome. [28][29][30][31][32] p53 Mutation leads to increased p53 protein stability and subsequent accumulation. One case study reports synchronous breast adenocarcinoma and DFSP, with the 2 lesions expressing similar levels of mutated p53.…”
Section: Discussionmentioning
confidence: 99%
“…D'autres auteurs incriminent les causes immunologiques telles que les chromosomes 22 annulaires qui occasionneraient une amplification de séquences des chromosomes 17 et 22 [10]. Minoletti et al décrivent une monosomie 22 [11] pendant que Diaz-Cascajo et al suspectent une intervention de la protéine p53 dans la pathogénie de l'affection [12]. Cliniquement, la lésion se présente comme une plaque indurée, recouverte d'une peau d'aspect et de coloration normale, parfois blanchâtre, blanc-jaunâtre, rosée, violacée ou rougeâtre, elle est apparemment bien délimitée et est mobile par rapport aux plans profonds.…”
Section: Discussionunclassified